Random-anisotropy effects in the second-order phase transition of the 2D Blume-Capel model - Nguyen, Quan D.; Bui, Son N.; Nguyen , H. Phong; Bach, H. Giang (Communications in Physics, 2025)
We report on the second-order phase transition of two-dimensional (2D) magnetic materials under the influence of random anisotropy in the context of the Blume-Capel model employing an effective field theory and the differential operator method. By analyzing the temperature dependence of magnetization, we thoroughly explore the second-order ferromagnetic-to-paramagnetic (FM-PM) phase transition at the critical temperature \(T_C\). When the magnitude of the random anisotropy \(D\) and its probability \(p\) is sufficiently large, the magnetization equation becomes divergent and unsolvable at a critical temperature, indicating the emergence of a tricritical point and a first-order phase transition. Additionally, we produce a phase diagram for the second-order phase transition presenting the relation between the critical temperature and the anisotropy amplitude at various probabilities.